Could climate change and urban growth make Europeans regard urban trees as an additional source of danger? - Portoghesi, Luigi; Masini, Emanuela; Tomao, Antonio; Agrimi, Mariagrazia (Frontiers in Forests and Global Change, 2023)
In some geographical areas of North America and Southeast Asia cities are frequently hit by heavy windstorms capable of knocking down hundreds of urban trees and large branches in a few minutes. Falling trees generate a broad array of disservices that vary over time and space. In Europe and worldwide the frequency of these extreme weather events has increased in recent decades and climate change could intensify these windstorms while the effects of urban land expansion could increase the extent of damage. However, Europe’s urban populations are unprepared for extreme weather events and are unable to limit the effects that the widespread loss of trees over limited space and time can have on people, buildings and city road networks. Preparing for rare, extreme future events that could strongly affect urban green infrastructures is a demanding challenge for city dwellers and for those who should ensure the continuity of the ecosystem services provided by urban trees. In fact, the damage caused by fallen trees is combined with the loss of the benefits provided by the trees themselves. Therefore the aim of this paper is to: (a) investigate the disruptions that a windstorm can cause in an urban area full of trees using a conceptual model; (b) conduct a literature review to determine how high the risk of these disservices occurring in Europe really is, which is definitely more likely than commonly perceived and could increase as a result of climate change and; (c) indicate what kind of measures can be taken in European cities to prevent or at least reduce the risks from falling urban trees during a strong windstorm, starting from the experience gained in the geographical areas most frequently and intensely affected by this type of weather event.